Determinants of Family Planning Unmet Needs in West Java and Policy Recommendations during the Covid-19 Pandemic (Based on Advanced Analysis of 2019 SKAP Data) - Larasanti, Ayudina; Ayuningtyas, Dumilah; Herartri, Rina Herartri; Naibaho, Margareth Maya Parulianta (UI Scholars Hub, 2021)
The Unmet Need for Family Planning (KB) in 2019 is still far from the 2015-2019 Strategic Plan target set at 9.91 percent. Seventeen provinces have a percentage of Unmet Need KB above the national figure (14.4 percent). One of them is WestJava Province, with a percentage of Unmet Need of 14.8%. Provinces with a high number ofUnmet Needs require the attention of policymakers, especially in the COVID-19 pandemic. West Java is the high-risk red zone category of COVID-19. Increased public awareness of the transmission of Covid-19 is an additional constraint to reducing the Unmet Need for family planning in the community. Therefore, it is necessary to analyze the determinants of Unmet Need as a basis for formulating policies on family planning services appropriate to be applied during the COVID-19 pandemic. This research used mixed methods with SKAP 2019 data as secondary data to identify determinants of Unmet Need for Family Planning inWestJava, and primary data in the formof in-depth interviews with family planning service stakeholders to explore the implementation of family planning services in West Java, including the COVID-19 pandemicsituation. Furthermore, multinomial logistic regression using in the data analysis. The results showed that the variables that had a statistically significant effect on Unmet Need Spacing were age (OR = 0.485) and never visits health facilities (OR = 1.616). While thevariables that have a significant effect on Unmet Need Limiting are the variable age (OR = 7.101), the number of living children more than 3 (OR= 1.466), ruralresidence (OR= 0.528),and the median wealth index (OR = 1.536)